Nanomechanical behaviour of green ceramics: Mg(OH)2 and MgO. Issue 23 (1st December 2022) - Chanda, Dipak Kr; Saha, Namrata; Ghosh, Chandan Kumar; Mukhopadhyay, Anoop K.
Abstract: The green ceramics are the fundamental basis for making the good quality sintered ceramics. Therefore, the present work explores how the microstructural variables such as the green density and volume percent open porosity affects nanomechanical properties evaluated for the nano Mg(OH)2 i.e., (NMOH) and the corresponding nano MgO i.e., (NMO) green ceramic compacts under similar experimental conditions. This is done by conducting nanoindentation (NI) experiments as a function of load (100–1000 mN) on the NMOH and NMO green ceramic compacts. For this purpose, the NMOH powder is hydrothermally synthesized using chemical precipitation route in presence of a surfactant. The NMO powder is obtained by heating the corresponding NMOH powder with the highest surface area. Characterizations by several conventional techniques such as X-ray diffraction, surface area measurement, nitrogen adsorption, field emission scanning electron microscopy, transmission electron microscopy etc. Help to identify the optimum microstructural condition to have the highest surface area. The results confirm the important role of green density, volume percent open porosity and crystal structure in determining the mechanical integrity of NMOH and NMO green ceramic compacts at the microstructural length scale.